2017
DOI: 10.18632/oncotarget.17456
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of using 18F-FDG PET and PET/CT in immunocompetent patients with primary central nervous system lymphoma: A systematic review and meta-analysis

Abstract: Background18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) and PET/CT have become two of the most powerful tools for malignant lymphoma exploration, but their diagnostic role in primary central nervous system lymphoma (PCNSL) is still disputed. The purpose of our study is to identify the usefulness of 18F-FDG PET and PET/CT for detecting PCNSL.ResultsA total of 129 patients, obtained from eight eligible studies, were included for this systematic review and meta-analysis. The performance of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 35 publications
0
52
1
Order By: Relevance
“…findings all together can mimic high-grade gliomas, metastatic tumors, tumefactive demyelinating lesions, or infectious and granulomatous diseases (54,55). Some studies suggest a role of advanced MRI and metabolic imaging such as FDG-PET in distinguishing primary central nervous system lymphoma from these entities (56). However, the histological analysis of biopsy material is still considered as the gold standard for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…findings all together can mimic high-grade gliomas, metastatic tumors, tumefactive demyelinating lesions, or infectious and granulomatous diseases (54,55). Some studies suggest a role of advanced MRI and metabolic imaging such as FDG-PET in distinguishing primary central nervous system lymphoma from these entities (56). However, the histological analysis of biopsy material is still considered as the gold standard for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Zou et al [32] showed that PET-CT was sensitive for PCNSL. In addition, PET-CT could determine the sensitivity of PCNSL to chemotherapy faster than MRI [33].…”
Section: Discussionmentioning
confidence: 99%
“…FDG uptake could be influenced by cumulative doses of corticosteroid before a PET scan, a point that should always be considered. A recent meta-analysis [ 73 ] on 18 F-FDG PET and PET/CT in PCNSL, based on 8 retrospectives studies (129 patients), revealed pooled sensitivity and specificity of 18 F-FDG-PET and PET/CT in the diagnosis of PCNSL of 0.88 and 0.86, respectively.…”
Section: Pcnsl Diagnosis: Role Of Petmentioning
confidence: 99%